First-In-Human Phase I Study of the OX40 Agonist MOXR0916 in Patients with Advanced Solid Tumors - Kim, Tae Won; Burris, Howard A; de Miguel Luken, Maria J; Pishvaian, Michael J; Bang, Yung-Jue; Gordon, Michael; Awada, Ahmad; Camidge, D Ross; Hodi, F Stephen; McArthur, Grant A; Miller, Wilson H; Cervantes, Andres; et al. (Clinical cancer research, 2022)
OX40, a receptor transiently expressed by T cells upon antigen recognition, is associated with costimulation of effector T cells and impairment of regulatory T-cell function. This first-in-human study evaluated MOXR0916, a humanized effector-competent agonist IgG1 monoclonal anti-OX40 antibody. Eligible patients with locally advanced or metastatic refractory solid tumors were treated with MOXR0916 intravenously once every 3 weeks (Q3W). A 3+3 dose-escalation stage (0.2-1,200 mg; n = 34) was followed by expansion cohorts at 300 mg (n = 138) for patients with melanoma, renal cell carcinoma, non-small cell lung carcinoma, urothelial carcinoma, and triple-negative breast cancer. MOXR0916 was well tolerated with no dose-limiting toxicities observed. An MTD was not reached. Most patients (95%) experienced at least one adverse event (AE); 56% of AEs, mostly grade 1-2, were related to MOXR0916. Most common treatment-related AEs included fatigue (17%), diarrhea (8%), myalgia (7%), nausea (6%), decreased appetite (6%), and infusion-related reaction (5%). Pharmacokinetic (PK) parameters were dose proportional between 80 and 1,200 mg and supported Q3W administration. The recommended expansion dose based on PK and OX40 receptor saturation was 300 mg Q3W. Immune activation and upregulation of PD-L1 was observed in a subset of paired tumor biopsies. One renal cell carcinoma patient experienced a confirmed partial response. Overall, 33% of patients achieved stable disease. Although objective responses were rarely observed with MOXR0916 monotherapy, the favorable safety profile and evidence of tumor immune activation in a subset of patients support further investigation in combination with complementary agents such as PD-1/PD-L1 antagonists.